Survival-Enhancing Learning in the Manhattan Hotel Industry, 1898–1980 - Baum, Joel A. C.; Ingram, Paul (Management Science, 1998)
In this study, we examine how experience at the level of the organization, the population, and the related group affects the failure of Manhattan hotels. We find organizational experience has a U-shaped effect on failure; that organizations enjoy reduced failure as a function of population experience before their founding, but not after; and that related organizations provide experience that lowers failure, but it matters whether their experience is local or non-local, and if it was acquired before or after the relationship was established. These results indicate both the difficulty of applying different types of experience to reduce the risk of organizational failure, and the relevance of experience for the evolution of organizational populations.